An innovative method for the microstructural modification of TiAl alloy solidified via direct electric current application. Issue 1 (January 2019) - Chen, Zhanxing; Ding, Hongsheng; Chen, Ruirun; Liu, Shiqiu; Guo, Jingjie; Fu, Hengzhi
Abstract: Ti-48Al-2Cr-2Nb alloy solidified with the application of direct electric current has a refined and homogeneous microstructure without segregation. We observed an initial decrease followed by a subsequent increase in grain size and lamellar spacing, with the increase in current density. Similar trend can also be obtained by varying the amount of α2 -phase (Ti3 Al). Using a directional solidification processing method, the columnar crystal microstructure transforms into an equiaxed crystal microstructure at a current density of 32–64 mA/mm 2 . High dislocation density is also introduced with a minimum cross-sectional grain size of 460 μm at a current density of 64 mA/mm 2 . The application of electric current alters the free energy of the critical nucleus and temperature via joule heating, causing a transformation from a columnar grain microstructure into an equiaxed grain microstructure. The increase in current density leads to a rise of the nucleation rate, and a resulting undercooling combined with temperature gradient contribute to growth of the primary phase, which finally results in grain coarsening at a critical current density of 96 mA/mm 2 . The climb and cross-slip of dislocation and the migration of grain boundary ultimately create variable lamellae spacing of TiAl alloy.